Methodological study protocol for The European Atlas of clinical trials in cancer and haematology - Cases, Mercè; Giles, Rachel; Ágh, Tamás; Piggin, Maria; Geissler, Jan; Racovita, Monica; Hagymásy, Judit; Ruth Wogu, Lora; Józwiak, Ákos; Hyseni-Bocolli, Albina; Hosszú, Dalma; Plate, Ananda; et al. (Frontiers in Pharmacology, 2025)
IntroductionInequalities in access to clinical trials in cancer, haematology and rare diseases, along with the inconsistent incorporation and reporting of patient reported outcome measures (PROMs) are a long-addressed issue by patient communities. The European Atlas on Clinical Trials in Cancer and Haematology (EuroACT) is a patient-led investigation assessing regional inequalities in access to clinical trials, the frequency and type of patient reported outcome (PRO) data collection in trials, and the reporting of PRO findings in selected solid tumours, malignant/non-malignant haematological conditions and rare diseases across Europe.Methods and analysisThis protocol outlines the development of three comprehensive datasets [i.e., clinical trials, patient reported outcome and experience measure (PROM, PREM), and publication datasets] along research questions and analysis plan for the EuroACT study. Data for the analysis were sourced from public clinical trial registries (e.g., EudraCT, ClinicalTrials.gov), PRO databases, and published literature, and were subsequently processed in several steps, including standardisation, enrichment, and merging. The analysis plan is organised into three workstreams, each focusing on hypotheses related to the geographical distribution of clinical trials, the use of PROMs in trials, and the frequency of PRO data publication, addressing multiple primary and sub-research questions. The EuroACT study has been co-developed with the patient community, involving a steering group of patient representatives at each step.ResultsA dataset of interventional trials and observational studies with European sites resulted containing 11,185 trials and 1.8 million data points for interventional trials, and 3,723 trials and 2,200 data points for observational studies. The PROM/PREM dataset contains information on 631 PROMs and 14 PREMs. The publication dataset development resulted in a comprehensive dataset containing information on 14,484 scientific publications.DiscussionThe EuroACT research project integrates high-quality data sources, including EudraCT and ClinicalTrials.gov (NCT), with advanced data processing techniques. The data access and processing workflows were developed to enhance transparency, reproducibility, and reliability, while also laying the groundwork for future automation efforts.